CRIP1 inhibits cutaneous melanoma progression through TFAM-mediated mitochondrial biogenesis - Jianqiang Wu; Lixia Chen; Peijun Wen (Scientific Reports)
Abstract Metastasis is the leading cause of death in patients with cutaneous melanoma. CRIP1 (cysteine-rich protein 1) has been reported to be associated with malignant progression of several cancers. However, the biological function and underlying mechanisms of CRIP1 in melanoma progression are largely unknown. Bioinformatic prediction of CRIP1 expression in melanoma and its association with clinical parameters and prognosis of patients. Real-time quantitative polymerase chain reaction (RT-qPCR) and Western blots (WB) were used to detect stable overexpression and knockdown of CRIP1 in melanoma cells. The function of CRIP1 in cutaneous melanoma cells was determined by in vitro functional assays. WB, immunofluorescence, OCR detection, mitochondrial DNA assay, and cytosolic ATP assay were used to determine the relationship between CRIP1 and mitochondrial biogenesis, relationship between TFAM. The expression level of CRIP1 in melanoma tissues is lower than that in normal tissues and suggests a poor prognosis for melanoma patients. Functionally, CRIP1 inhibits the proliferation, migration, and invasion of melanoma cells in vitro. Mechanistic studies revealed that CRIP1 inhibited mitochondrial biogenesis in melanoma cells, which included suppression of relative mitochondrial content, mitochondrial DNA copy number, ATP production, respiratory capacity, and expression levels of oxidative phosphorylation-related proteins. Further studies revealed that CRIP1 inhibits mitochondrial biogenesis and malignant progression in melanoma cells by suppressing the protein levels of TFAM. Our results suggest that CRIP1 inhibits the proliferation and invasive ability of cutaneous melanoma cells by suppressing TFAM-mediated mitochondrial biogenesis. Therefore, CRIP1 may be a potential therapeutic target for melanoma.